KI HAJAR DEWANTARA DAN KONSEP PENDIDIKANNYA DALAM PERSPEKTIF ISLAM - Zt, A. Masor (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
Ki Hajar Dewantara is an outstanding Indonesian hero. He is a prominent political figure in the movement for independence and at the same time a cultural figure and an expert in journalism. He is the founding father in education and was successful in the formulation of the concept of national education. So far, many people think that his concept of education is nationally-oriented at best. The fact is that some of his concepts in education had been inspired by Islamic educational principles. Any study on Ki Hajar Dewantara and his concepts of education seen from the point of view of Islamic doctrines should be carefully conducted so as to avoid any misunderstanding and misinterpretation. This article, which is an abstract and modification from the writer's dissertation, used Islamic point of view to study Ki Hajar Dewantara and his notion of education. In great details, the article studied the phenomena of Ki Hajar Dewantara in relation to Islamic doctrines, his concepts of education seen from Islamic education perspectives, his view on religious education and his view on the relevancy between his moral education and Islamic moral and character education.